SAT0119 Comparison between Carotid Plaque and Carotid Intima Media Thickness To Detect Subclinical Atherosclerosis in Rheumatoid Arthritis. (15th July 2016) - Riancho-Zarrabeitia, L.; Corrales, A.; Santos-Gόmez, M.; Portilla, V.; Blanco, R.; Dessein, P.; González-Gay, M.A.
Abstract : Background: Carotid plaque (CP) detected by ultrasonography and carotid intima-media thickness (cIMT) are useful surrogate markers for subclinical atherosclerosis and good predictors of cardiovascular disease in the general population and rheumatoid arthritis (RA). Objectives: Our aim was to determine if cIMT may predict the presence of carotid plaques. Methods: We evaluated 670 RA patients from NW Spain without previous history cardiovascular events. Carotid ultrasonography was performed by a MyLab 70 scanner (Esaote; Genoa, Italy), equipped with 7–12 MHz linear transducer and the automated software guided technique radiofrequency – Quality Intima Media Thickness in real - time ( QIMT, Esaote, Maastricht, Holland ). The cIMT was determined as the average of three measurements in each common carotid artery. The final cIMT was the largest average cIMT (left or right). Carotid plaque was defined according to the Manheim Consensus Conference criteria. Based on studies reported in non-rheumatic patients, a cIMT was considered as associated with high cardiovascular risk if it was ≥0.90 mm. Results: Unilateral and bilateral carotid plaque frequency and cIMT values are summarized in table 1 . cIMT values were 0.619±0.105 mm in patients without plaques and 0.774 ± 0.161 mm in those with plaques (p<0.001). Using 0.90 mm as the cIMT cut-off value for high cardiovascular risk, the sensitivity to detect carotid plaques was 21.2% and the specificity 99%. A ROC curve comparing the presence of carotid plaque and cIMT was performed, being the area under the curve 0.795. The best cIMT cut-off point to determine the presence of plaques was considered as the one with the highest sensitivity and specificity. According to that, 0.670 mm was found to be the best cut-off point, being sensitivity and specificity for plaque detection 71.9% and 74% respectively. Positive predictive value for a cIMT ≥0.670 mm was 78.3% in our population, being 66.8% the negative predictive value. Regarding bilateral plaques, a cIMT cut-off value of 0.90 mm had sensitivity of 27.7% and specificity of 96.6%. The ROC curve showed that the best cut-off point for bilateral plaque detection was also 0.670 mm with sensitivity 79.1% and specificity 64.2%. Conclusions: In Spanish RA patients cIMT ≥0.670 mm is a good predictor of carotid plaques. Our study suggests the possibility of considering a cIMT lower than 0.90 mm as a predictor of high cardiovascular risk in RA. Disclosure of Interest: None declared